Education, prospection and social networks: surveying ideas-engagement amongst 7,000 respondents across seven European countries - Chris Brown; Ruth Luzmore; Yin Wang (Quality Education for All)
Purpose – This study aims to present efforts by the research team to develop a new survey instrument measure ideas-engagement that explores patterns of ideas-engagement across seven European countries, assessing how each performs in relation to the key criteria of education, social networks and a prospective mindset as well as the value placed by respondents on engaging with ideas. The authors also examine the extent to which respondents engage with ideas effectively. Design/methodology/approach – The authors operationalised a previously developed theoretical framework: developing a survey instrument, the Ideas Networks Prospection and Education Survey and administering this to 1,000 participants per country (7,000 respondents in total). The survey explores factors influencing ideas engagement, including the respondents’ educational background, social networks and forward-looking attitudes. Descriptive analysis examines variations in these factors across cultural and national contexts.Results provide country profiles for education, prospection and social network characteristics as well as ideas-engagement. Countries with higher individualism and long-term orientations, such as Sweden and Finland, exhibited stronger critical engagement with ideas, whereas more collectivist nations like Italy and Spain demonstrated larger networks but lower criticality scores. Originality/value – This study operationalises a novel theoretical framework for understanding ideas-engagement and explores how cultural and individual factors shape engagement with both beneficial and harmful ideas. By comparing diverse European nations, the study provides an initial analysis of the complex interplay between cultural dimensions and individual tendencies in shaping an ideas-informed society. This framework supports future research and interventions aimed at enhancing informed decision-making and critical engagement in the face of misinformation.